Line plots of performance metrics across TFIDF conditions. - Stefan Saverimuttu (20882325) (2025)
Mean (y-axis) of recall, precision, and F1-score (as labelled) of all testers, for each clinicopathologic finding (key), across the four TFIDF conditions (x-axis) tested in a pilot test of the application, DEE, designed for extraction of necropsy data from the Wildbase Pathology Register.